(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The world is currently witnessing a boom in the gig economy due to frequent market disruptions, technological advancement, and the aspirations of the millennials. There is a win-win situation for both employers and gig workers. Employers are excited about the reduced cost of employment and gig workers are excited due to increased freedom, flexibility, and finances. However, on the flip side is the lack of responsibility to manage the skill level with the technological advancement, and the future requirements of the market. The growing skill mismatch is obvious and calls for skill development of the gig workers for the success of the gig economy. The study has made an effort to understand the gig economy in India, its salient features and has deliberated on various aspects of the skill development for the gig workers like skill requirements, challenges involved and various strategies of skill development. The study has concluded that Gig workers need to understand their own responsibility towards upskilling themselves and keep learning to remain relevant. Employers should also understand their responsibility in skilling gig workers and familiarize them with the organization’s goals, strategy, culture, and operations. At the same time, they need to train their regular employees on collaborating with the gig workers so that both these groups may operate cohesively while acknowledging and respecting one another's unique work ethos. The government needs to bring in the required policy framework to create a conducive environment for the gig economy. The success of the gig economy depends on the cohesive and collaborative efforts of both these groups of employees, employers and the Government.